Analisis Kinerja Keuangan pada Perusahaan Sektor Pertambangan Yang Terdaftar BEI dalam Indeks LQ-45 Periode 2019-2021 - Febriyanti, Tika; Syarifudin, Akhmad (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2023)
This research aims to determine the financial performance of mining sector companies listed on the IDX on the LQ-45 index for the 2019-2021 period. Measurement of liquidity ratios uses the current ratio, quick ratio and cash ratio proxies. Meanwhile, profitability ratios are used as ROA, ROE and NPM proxies. This type of research is quantitative descriptive using secondary data sources obtained from the websites of each mining company. The results of the research show that the ADRO company has liquidity conditions from the quick ratio and cash ratio (categorized as very good), but the current ratio (categorized as poor). At the ANTM company the liquidity conditions from the current ratio and quick ratio (categorized as poor), but the cash ratio ( categorized as very good). For INCO, ITMG and PTBA companies, liquidity conditions in terms of current ratio, quick ratio and cash ratio (categorized as very good). Meanwhile, from the general profitability ratios of ROA, ROE and NPM for the 2019-2021 period in all mining sector companies ADRO, ANTM, INCO, ITMG and PTBA (in the poor category), this is because sales, income and sales prices have decreased so that profits decreased but did not result in losses.